THE BIOTECHNOLOGY AND THE AMAZONIA BIODIVERSITY CONSERVATION, ITS IMPACT ON ENVIRONMENTAL POLICIES - Barbosa, Francisco Benedito da Costa (Science & Technology Journals, 2001)
This article describes the possibility to add the modern biotechnology, as a way of Amazonian biodiversity conservation and its insertion in environmental policies, creating synergies with the development policies applied in the region, in the search of the sustainability.